2016
DOI: 10.18632/oncotarget.8443
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus oncogenic E6 protein regulates human β-defensin 3 (hBD3) expression via the tumor suppressor protein p53

Abstract: Human β-defensin-3 (hBD3) is an epithelial cell-derived innate immune regulatory molecule overexpressed in oral dysplastic lesions and fosters a tumor-promoting microenvironment. Expression of hBD3 is induced by the epidermal growth factor receptor signaling pathway. Here we describe a novel pathway through which the high-risk human papillomavirus type-16 (HPV-16) oncoprotein E6 induces hBD3 expression in mucosal keratinocytes. Ablation of E6 by siRNA induces the tumor suppressor p53 and diminishes hBD3 in HPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…A recent study showed that hBD3 expression was regulated by the high-risk human papillomavirus E6 protein via p53 in oral squamous cell cancers [21]. This intriguing finding prompts the question whether hBD3 is expressed in another HPV-inducing cancer, cervical cancer and if so, whether hBD3 plays a role in the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that hBD3 expression was regulated by the high-risk human papillomavirus E6 protein via p53 in oral squamous cell cancers [21]. This intriguing finding prompts the question whether hBD3 is expressed in another HPV-inducing cancer, cervical cancer and if so, whether hBD3 plays a role in the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has gradually been shown that a number of human cancers of squamous keratinocytes (e.g. cervical, esophageal, salivary gland, head and neck carcinoma, colon, etc) show elevated expression of β‐defensin 2 and/or 3 . Both β‐defensin 2 and 3 promotes tumor cell proliferation and/or invasion .…”
Section: Alarmins and Tumor Immunitymentioning
confidence: 99%
“…[194][195][196][197][198][199] Both β-defensin 2 and 3 promotes tumor cell proliferation and/or invasion. 194,197,198 β-defensin 3 upregulation can be triggered by either epidermal growth factor or human papillomavirus 199 and its promotion of tumor cell proliferation involves the activation of NF-κB. 198 In contrast, human β-defensin 1 has been shown to inhibit the proliferation of several types of cancer cells.…”
Section: Defensinsmentioning
confidence: 99%
“…TNM and UICC stages are generally still used to describe the size of the tumour and its invasion into the lymphatic system from a topographic point of view, although recently, these systems were shown to be poor at accurately predicting an outcome [4, 5]. The latter classifications of OSCC are used for outcome prediction and decision-making concerning additional radiotherapy in cases of positive nodal metastasis [6]. Therefore, the need to detect reliable predictive biomarkers, genetic alterations or epigenetic modifications in OSCC to estimate recurrence for therapy stratification and planning is significant, and it is also important to identify significant molecular pathways to precisely select patients who are suitable for additional therapy [79].…”
Section: Introductionmentioning
confidence: 99%